KAJIAN PENGARUH KONSENTRASI Rhizopus sp. SEBAGAI AGEN PENGIKIS PROTEIN TERHADAP MUTU KULIT IKAN GURAMI TERSAMAK - Ratri Nur Hayati (Universitas Gadjah Mada, 2013)
The study aimed to assess the effect of protease activity of Rhizopus sp. as a bating agent on the tanned carp leather quality, and their use for commercial leather products. The study was designed with a completely randomized design with four treatment, namely: the concentration of protease from Rhizopus sp. 0.5% (a1), 1.0% (a2), 1.5% (a3) and palkobat 1.0% (a4/control) with 3 replications. Parameters were observed that is (1) protease activity of Rhizopus sp and palcobat; (2) Thickness (mm), tensile strength (N/cm2), tear strength (N/cm), elongation (%), enervation (mm), shrinkage temperature (ºC), fat/oil content (%) of tanned leather; and (3) level of consumer acceptance (%) and added valuead of comercial leather product. The data of tanned leather quality is then compared with SNI 06-4586-1998 concenring freshwater snake skin leather and chrome Burk’s Bay (1996) on the raw material quality leather products. The test results of protease activity of Rhizopus sp. = 7.97 mg/50mg/ jam and palkobat = 13.62 mg/50 mg/hour. The results of the analysis of tanned leather carp qulity sample from each treatment and comparison with the SNI as follows: (1) Thickness: 0.41 (a1), 0.38 (a2), 0.43 (a3), 0.41mm (a4) and ≥ 0.22 (SNI 06-4586-1998). Tensile strength: 1682.67; 1818.17; 1195.57; 1670.55 and 1,000N/cm2 (SNI). Tear strength: 314.87; 310.95; 332.06; 462.22, and 150.00 N/cm (SNI). Elongation: 93.33; 62.67; 56.67; 97.33, and <30.00% (SNI). Enervation: 1.87; 2.20; 1.63, 2.49, and ≥ 2.0 mm (Burk’s Bay, 1996). Shrinkage temperature: 74.00; 95.33; 96.33; 97.33, and ≥ 70.33ºC (SNI). The fat/oil content: 7.84; 8.17; 5.25; 8.49, and 2.00 to 6.00% (SNI). All treatments were tested has met the SNI quality, except elongation and fat/oil content. The level of consumer acceptance of the Oval HP Cover that is (1) aspects of the display (76.67% like and 23.33% dislike), (2) the use of convenience (66.67% like and 33.33% dislike ), and (3) price (63.33% accepted and 23.67 reject). The level of consumer acceptance of the Box Cover HP models that is (1) aspects of the display (80.00% like and 20.00% dislike), (2) convenience of use (86.67% like and 13.33% dislike), and (3) price (66.67% accepted and 33.33% reject). The economic value of tanned carp leather as big as Rp 160.000/20 leather pieces and leather products as big as Rp 420,000 per 15 pieces of product.